Caracterização parcial do extrato enzimático bruto de gengibre e seu efeito na fragmentação de miofibrilas em carne de frango - Cruz, Pamela Lemos (2018)
The application of proteases is of great interest to the food industry and ginger is one of the plant sources from which a cysteine protease is obtained and which has application in improving meat texture. In this context, the present study aimed to characterize the crude enzymatic extract of ginger, to evaluate its proteolytic activity in myofibrillar proteins extracted from the Pectoralis major muscle of broiler chicken. Afterwards, three treatments were applied to evaluate its effect on the chicken breast: Control (chicken breast), breast of chicken added of 5% (w/v) of 100 mM phosphate buffer (pH 7.0) and breast of chicken added with 5% (w/v) of crude ginger enzymatic extract. It was determined instrumental texture, myofibrillar fragmentation index (MFI), length of myofibrillar fragments (MFL), sarcomere length and cooking loss. The crude enzymatic extract of ginger showed an optimum temperature of 60 °C and an optimum pH of 5.5. The crude enzymatic extract of ginger showed residual activity of 55.4% at 70 °C and more than 55% at pH ranging from 6 to 8. In the kinetic study with azocasein as a substrate, Vmax values of 23.50 U. mL-1 and Km of 3.47 mg. mL-1 were obtained. For the myofibrillar extract as substrate, values for Vmax of 1.29 U.mL-1 and Km of 21.48 mg. mL-1 were found, indicating a lower specificity of the crude ginger enzymatic extract by this substrate. There was no significant difference (p=0.05) between treatments for sarcomere length and cooking loss. There was a reduction in the value of instrumental texture (p<0.05) and an increase in the myofibrillar fragmentation index (p<0.01) of the treatment with 5% (w/v) crude ginger enzymatic extract compared to the other treatments. Phase contrast microscopy showed that the samples treated with 5% (w/v) crude ginger enzymatic extract presented myofibrils with a higher degree of fragmentation compared to the other treatments, with a length of 4.542 µm, 11.324 µm (Control) and 10.893 µm for chicken breast added with 5% of 100 mM phosphate buffer (pH 7.0). Therefore, the application of 5% crude enzyme extract of ginger in chicken breast promoted the fragmentation of the myofibrils and the reduction of the shear force without excessively altering the texture of the meat and resulting in a increase in the cooking loss of the samples.